Influence of Islamic Studies Pedagogy on Student’s Achievement in Kazaure Madrasas, Jigawa State, Nigeria - Zaharaddeen Umar (Al-Fadlan: Journal of Islamic Education and Teaching, 2025)
This study investigates the influence of Islamic Studies pedagogy on students’ achievement in Kazaure Modern Madrasas, Jigawa State. The research focuses on three key objectives: to examine the principles and practices of modern Islamic education, to find out the socio-emotional dimensions affecting students’ learning experiences, and to identify the factors influencing students’ academic achievement in the selected Madrasas. A mixed-method research design was adopted, combining qualitative and quantitative approaches to provide a comprehensive understanding of the pedagogical impact. The study used sample size of 150 respondents. Data were collected through questionnaires, interviews, and classroom observations; it was analyzed using descriptive statistics (frequencies, percentages and mean) with the aid of statistical package for social sciences (SPSS Version 21.0). Findings revealed that the effective application of Islamic pedagogical principles—such as moral instruction, teacher-student interaction, and learner-centered approaches—significantly enhances students’ cognitive and spiritual development. Moreover, socio-emotional factors such as motivation, teacher empathy, and peer relationships were found to play a vital role in shaping students’ attitudes and performance. The study also identified challenges including inadequate instructional materials, teacher training gaps, and limited institutional support. It concludes that strengthening modern Islamic pedagogical practices can improve both academic and moral outcomes among Madrasa students. Recommendations were made for educators, policymakers, and Islamic institutions to integrate holistic teaching approaches that balance religious and modern educational objectives for sustainable student achievement.